2012
DOI: 10.4067/s0716-97602012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in quality and fertility of porcine semen

Abstract: The aim of this study was to investigate the eff ect of boar age on quality traits and fertility of liquid-stored semen. Boars were allocated into 3 age groups: 7-10 months (young), 18-33 months (mature), 51-61 months (old). Ejaculates of ≥ 200x10 6 sperm/ml and 85% total motile sperm were extended to 30x10 6 sperm/ml, stored at 17-18 °C and used within 12-24 h for artifi cial insemination (AI) of 2062 multiparous sows. After 24 h of storage, aliquots of diluted semen were assessed for sperm progressive motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
(18 reference statements)
2
14
0
2
Order By: Relevance
“…After reaching the age of 3 years, the numbers of spermatozoa in ejaculate recorded a decrease to 101.71 bn in the case of total number of spermatozoa and 66.81 bn in the case of corrected number of spermatozoa (p < 0.05). Many authors have stated that quality of boar semen increased with age (Bonet et al, 2013;Kumaresan et al, 2011;Tsakmakidis et al, 2012), which is confirmed in this work, but only up to 3 years of age. According to Bonet et al (2013), Zduńczyk et al (2011) and Araujo and Wittert (2011), the production of spermatozoa depends on the testosterone level, which varies during testicular development, puberty and sexual maturity.…”
Section: Resultssupporting
confidence: 71%
“…After reaching the age of 3 years, the numbers of spermatozoa in ejaculate recorded a decrease to 101.71 bn in the case of total number of spermatozoa and 66.81 bn in the case of corrected number of spermatozoa (p < 0.05). Many authors have stated that quality of boar semen increased with age (Bonet et al, 2013;Kumaresan et al, 2011;Tsakmakidis et al, 2012), which is confirmed in this work, but only up to 3 years of age. According to Bonet et al (2013), Zduńczyk et al (2011) and Araujo and Wittert (2011), the production of spermatozoa depends on the testosterone level, which varies during testicular development, puberty and sexual maturity.…”
Section: Resultssupporting
confidence: 71%
“…This finding is supported by the observation that for NL boars, the level of DNA fragmentation decreases by increased boar age. A recent study has reported a lower incidence of chromatin instability in semen from mature boars (18–33 months) compared to young boars (7–10 months) and old boars (51–61 months) (Tsakmakidis, Khalifa, & Boscos, ). In comparison, our samples are limited to the young and mature age groups, and for NL boars, our results are in accordance with the observation by Tsakmakidis et al ().…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported a lower incidence of chromatin instability in semen from mature boars (18–33 months) compared to young boars (7–10 months) and old boars (51–61 months) (Tsakmakidis, Khalifa, & Boscos, ). In comparison, our samples are limited to the young and mature age groups, and for NL boars, our results are in accordance with the observation by Tsakmakidis et al (). Sampling of Duroc semen in this study was stopped at an even lower age due to more frequent change of boars in the breeding system used, which may have influenced a lack of significant age effect on the DFI levels.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular measurements are one of these characteristics, and their measurement varies with boar age (Fraser, Strzezek, Filipowicz, MogieInicka‐Brzozowka, & Zasiadczk, ; Savić, Petroviý, Rodojković, Radović, & Parunović, ; Schulze, Buder, Rüdiger, Beyerbach, & Waberski, ; Tsakmakidis, Khalifa, & Boscos, ) and the time of the year (Fraser et al, ; Górski, Kondracki, & Wysokińska, ; Sancho et al, ; Torre et al, ; Zasiadczyk, Fraser, Kordan, & Wasilewka, ). Testicular measurements have been used in testicle weight prediction (Davis & Hines, ; Ford & Wise, ), and these measurements have been previously correlated with sperm quality and spermatogenesis (Clark, Schaeffer, & Althouse, ; Jacyno, Kawęcka, Pietruszka, Sosnowska, Kawęcka, Pietruszka, & Sosnowska, ; Savić et al, ).…”
Section: Introductionmentioning
confidence: 99%